VENA CAVA LEIOMYOSARCOMA DEVELOPING BUDD CHIARI SYNDROME: CASE REPORT - Puppo, Mariana Brasileiro Vieira (2023)
Vena cava leiomyosarcoma is a rare neoplasm, usually divided into 3 types: Type I- below the renal vein, Type II- between the renal and hepatic veins and Type III - between hepatic veins and right atrium. In Type III venous drainage of the liver is compromised and may be the etiology of Budd Chiari Syndrome. Radiological imaging is very characteristic and may be the key to diagnosis. The aim of this case report is to present a 68-year-old patient, male, with severe abdominal pain associated with ascites, lower limb edema and portal hypertension compatible with Budd Chiari Syndrome. Tomography showed infiltrative image in the inferior vena cava pathway extending to the caudate lobe of the liver and histology showed low-grade leiomyosarcoma, confirmed by immunohistochemistry. Knowing the clinical and radiological picture of vena cava leiomyosarcoma allows doing the diagnosis and guiding the treatment and prognosis, reducing the economic and emotional costs.